Inovação e resistência: uma análise do ensino da matemática em uma escola pública - Ribeiro, Dilson Ferreira (2013)
This thesis aims to develop a study that allows understanding why some math teachers are tough on the possibilities of changes that occur in their area of expertise. Changes that establish a relation between innovation and teaching methodology, through the possibility of diversifying its evaluation instruments. It's made a study of factors considered responsible for teachers' attitudes, contrary to innovation in teaching mathematics as their working conditions or their experience of the classroom throughout his career, beginning even in their basic training. For this, we made an approach relating the strength and innovation, Teaching Traditional and Innovative Education, through the study of Organizations National Curriculum of Secondary Education, from the changes proposed by the state government of Rio Grande do Sul in relation to basic education. The field research was empirically chosen the College Municipal Pelotense, place of work of the author, with the participation of seven mathematics teachers of high school. Respondents discussed the possibilities of change in mathematics education from meetings that provided activities. These meetings were offered in the second half of 2012 with its height at the beginning of the school year of 2013 with the implementation of a teaching methodology different from that used by teachers and stood as the final product of this dissertation. Amid the conclusions is possible to highlight some factors that lead to resistance changes in the teaching of mathematics, among them there are the working conditions and educational policies , factors responsible for some teachers they dislike what can be called innovation in the classroom class . When it comes to innovation , the possibility exists since it is provided , and an infrastructure capable of offering the teacher a good working environment with the provision of resources and physical space , moments of discussions about their practice and appreciation or acknowledgment of their ability creative .